HAb18G/CD147 Regulates Vinculin-Mediated Focal Adhesion and Cytoskeleton Organization in Cultured Human Hepatocellular Carcinoma Cells - Liang, Qiang; Han, Qing; Huang, Wan; Nan, Gang; Xu, Bao-Qing; Jiang, Jian-Li; Chen, Zhi-Nan (PloS one, 2014)
Focal adhesions (FAs), integrin-mediated macromolecular complexes located at the cell membrane extracellular interface, have been shown to regulate cell adhesion and migration. Our previous studies have indicated that HAb18G/CD147 (CD147) is involved in cytoskeleton reorganization and FA formation in human hepatocellular carcinoma (HCC) cells. However, the precise mechanisms underlying these processes remain unclear. In the current study, we determined that CD147 was involved in vinculin-mediated FA focal adhesion formation in HCC cells. We also found that deletion of CD147 led to reduced vinculin-mediated FA areas (P<0.0001), length/width ratios (P<0.0001), and mean intensities (P<0.0001). CD147 promoted lamellipodia formation by localizing Arp2/3 to the leading edge of the cell. Deletion of CD147 significantly reduced the fluorescence (t1/2) recovery times (22.7±3.3 s) of vinculin-mediated focal adhesions (P<0.0001). In cell-spreading assays, CD147 was found to be essential for dynamic focal adhesion enlargement and disassembly. Furthermore, the current data showed that CD147 reduced tyrosine phosphorylation in vinculin-mediated focal adhesions, and enhanced the accumulation of the acidic phospholipid phosphatidylinositol-4, 5-bisphosphate (PIP2). Together, these results revealed that CD147 is involved in vinculin-mediated focal adhesion formation, which subsequently promotes cytoskeleton reorganization to facilitate invasion and migration of human HCC cells.